Tuberculosis of Cystic Lymph Node of Lund-A Rare Presentation - Paul, TK; Baqui, MN; Parveen, R (Journal of Surgical Sciences, 2019)
Tuberculosis is one of the major infectious diseases in Bangladesh. After respiratory system, lymphatic and gastrointestinal tracts are the commonest sites of development of this pathology. However, hepatobiliary tuberculosis is rare, seen in approximately 1% of all abdominal cases. Reporting of tuberculosis of the cystic duct lymph node is very uncommon. Its diagnosis is difficult because of the absence of characteristic symptoms and signs. In this case report, we present a case of tuberculosis of cystic duct lymph node. Journal of Surgical Sciences (2013) Vol. 17 (1) : 62-63